Educação física e saúde: conhecimentos e concepções advindas no contexto do ensino médio - Jesus, Rhenan Ferraz de (2018)
The present study had as objective to analyze how the health theme has been approached in the Physical Education (EF) in High School (EM), from the perceptions in school documents and from the perspective of EF teachers and students. This is an exploratory case study. A literature review was performed. We analyzed materials that guide educational practices (Pedagogical Administrative Political Project - PPAP, Physical Education Study Plans - PEEF, and Physical Education Clubs - CEF). Complementing the collected materials, we conducted semi-structured interviews with four teachers of EF and applied a questionnaire to 134 students of EM. The analysis method used was content analysis. In general, the results lead us to point out that the treatment of the health theme is given: a) educational proposals (Pedagogical Administrative Political Project, Physical Education Area Study Plan and Physical Education Clubs) give more emphasis to the understanding of the category of analysis Social relations and communication, as essential for creating dialogues around school health issues; b) in the teachers' report, this emphasis is broadened in the approach of several conceptual aspects (category Concepts and convictions) and procedural ones (Competences category), most of them being based on the disease, such as a concern to alert students about the possible health risks due to the adoption of habits and behaviors in health not so healthy; and c) by the students' view, health has been understood more in the treatment of the categories of analysis Competences and Behaviors and lifestyle, mainly, to aspects of the practice of activities that involve motor actions of its practitioners. From the study carried out in the investigated context, it was concluded that the treatment of the health theme has been understood differently between the documents analyzed, to the perspective of the teachers of EF and, also, to the perception of the students of EM. This observation allows us to analyze that in the school studied, not always what is articulated around the health theme, both in the analysis of the educational proposals of the school and in the area of Physical Education, as well as the teachers' conceptions, can be easily understood by the students, as systematized and organized in the pedagogical work of the school and the teachers.